'Chinese' Indonesians in National Cinema - Sen, Krishna (Routledge, part of the Taylor & Francis Group, 2006)
Through much of post-colonial history and particularly during the so-called 'New Order' (under General Suharto), Indonesian citizens of ethnic Chinese descent have been caught in a strangely ambiguous position: they have enjoyed enormous economic power while at the same time being threatened with politico-cultural effacement. This paper is an attempt to understand that ambiguity in relation to the Indonesian cinema both around questions of industry history and around issues of representation of national and ethnic identity on screen. The paper traces the presence, the erasure and the absent-presence of Indonesia's ethnic Chinese minority from the establishment of a film industry in Indonesia in the 1930s to the post-New Order political shifts, opening up possibilities for a new public discourse of Chineseness. I argue however that the openness of current Indonesian culture and politics while providing the necessary condition for re-imagining the Chinese Indonesians, does not ensure a radical shift in a politics of representation, deeply embedded in the textual practices of the film industry and more widely in cultural and political history of modern Indonesia.